UNESCO and UNICEF’s Human Rights-Based Approach towards EFA goals, Economically Wise or Irrational: Policy Analysis from Economic Perspective - Korwatanasakul, Upalat (Global and Policy Journal of International Relations, 2015)
ABSTRACTAn analysis is given of UNESCO and UNICEF’s current thinking and practice in the education sector, especially on a human rights-based approach. Economically irrational policy implementation can be a result of inefficiency and ineffectiveness of resource allocation; therefore, policy assessment is necessary. Moreover, the deadline for EFA goals is approaching and it seems that EFA goals will not be met under current policy implementation by 2015. This paper bases its analysis on economic theory and offers policy implications and suggestions through a thought experiment and empirical case studies. An analysis is conducted in two levels, general perspective on education and specific aid projects/programmes. Analysing policies from economic perspective gives a new impression and dimension towards UNESCO and UNICEF. This paper argues that a human rights-based approach is economically rational and sustainable. Identifying rights-holders and duty-bearers cannot only induce demand and supply for education but also theoretically make individuals’ demand for education to be more inelastic to the prices or costs of education. However, in terms of effectiveness of project/programme investment, adjustments are required in the process of project/programme implementation. As a result, there is an ambiguous tension between theoretical and practical issues. Policy implications and suggestions are made accordingly.Keywords: Policy analysis, Human rights-based approach, Multilateral donor agenciesDOI:https://doi.org/10.33005/jgp.v3i02.1932